16.4k views
3 votes
Which equation is equivalent to

Which equation is equivalent to-example-1

2 Answers

6 votes

For this case we place the terms with "x" on the left side of the equation, and the terms without "x" on the right side:


\frac {2} {3} x + \frac {5} {12} x = \frac {1} {4} + \frac {5} {6}

We add similar terms:


\frac {24 + 15} {36} x = \frac {6 + 20} {24}\\\frac {39} {36} x = \frac {26} {24}

We simplify both sides:


\frac {13} {12} x = \frac {13} {12}

Dividing by
\frac {13} {12} on both sides of the equation:
x = 1

Answer:


x = 1

User Kburbach
by
5.7k points
5 votes

Answer:

Simplifying the equation:


(2)/(3) x - (5)/(6) = -(5)/(12) x + (1)/(4)

Grouping like terms:


(2)/(3) x + (5)/(12) x= (1)/(4) + (5)/(6)


(39)/(36) x=(26)/(24)

Solving for 'x', we have:


x=(26)/(24)(36)/(39)=1

User Chea Sambath
by
4.9k points